Uterine lipoleiomioma - Reyna-Villasmil, Eduardo (2022)
Lipoleiomyoma is a rare benign uterine neoplasm whose incidence varies between0.03%-0.2%. This tumor is considered a benign variant of typical uterine leiomyomas.It consists of a variable proportion of mature adipocytes and smooth muscle cells.The etiology may be related to estrogen deficiency occurring after the menopausaltransition; it usually appears in obese perimenopausal or menopausal women. Thesymptomatology is nonspecific, and most are diagnosed incidentally. We present acase of uterine lipoleiomyoma in a 45-year-old patient who consulted for abdominalpain. Ultrasonography showed a tumor in the anterior wall of a homogeneousand well-defined uterus. During laparotomy, a yellowish tumor with a soft texturewas found. Total hysterectomy plus oophorosalpingectomy was performed. Theanatomopathologic diagnosis was uterine lipoleiomyoma.